2006
DOI: 10.1007/s00402-006-0151-4
|View full text |Cite
|
Sign up to set email alerts
|

Severity of injuries associated with femoral fractures as a result of motor vehicle collisions

Abstract: Concomitant injuries are to be expected in the majority of cases of femoral fractures sustained as a result of MVCs. There should be a low threshold for involving a general surgical team in the management of these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…8 However, these studies included only automobile trauma and were skewed toward more severe injuries. 4,9 Similar studies have demonstrated injury associations. Adili et al showed an association of humerus fractures in motor vehicle collisions with other musculoskeletal injury, as well as liver injuries.…”
Section: Introductionmentioning
confidence: 57%
“…8 However, these studies included only automobile trauma and were skewed toward more severe injuries. 4,9 Similar studies have demonstrated injury associations. Adili et al showed an association of humerus fractures in motor vehicle collisions with other musculoskeletal injury, as well as liver injuries.…”
Section: Introductionmentioning
confidence: 57%
“…1,2 Injuries are prioritized based on threat to life, with the additional orthopedic goal of skeletal stabilization to achieve early mobilization. Femoral shaft fractures are not uncommon in these types of traumatic mechanisms, 1,2 and operative fixation is often necessary to stabilize the fracture. 2 Residual hip pain can be present in some patients after appropriate healing of the femoral shaft fracture.…”
mentioning
confidence: 99%
“…Αρκετοί ερευνητές έχουν μελέτησει αυτά τα πρότυπα συνοδών κακώσεων ή πιθανές συσχετίσεις με κακώσεις σε συγκεκριμένες ανατομικές περιοχές [94][95][96][97].…”
Section: εισαγωγήunclassified